Validity testing of a tool measuring awareness of patients' right in a tertiary hospital - Reyes, Kimberly Rose; Rodriguez, Harriet Marie; Salem, Aina Fe; Serquina, Bless Noelle; Sia, Rani Aidelind; Tambio, KristanJela; Tiongco, Ana Rosalia; Zapanta, Rachel Ann
This study aims to develop a research instrument for patients in a tertiary hospital which intends to facilitate the description of patients’ rights awareness in a tertiary hospital. The tool was developed through extensive literary synthesis. First, a triangulation of the similar categories found in the respective policies regarding patients’ rights of one continent, Europe, and 5 countries namely Australia, Israel, Philippines, South Africa, and Turkey, was done. Using the data from the triangulation, the patients’ rights in the Philippine General Hospital were defined, After integrating the results from previous literature done on the topic and the definition of the identified rights, constructs were formulated and found to be valid upon being subjected to construct validation by three experts. A cumulative validity index was then used to measure the construct validity of the devised situations. After the computation of the CVI and filtering the 56 constructs, 20 were considered as valid and were used for the final tool. By knowing the status of patients’ awareness of their rights, it is easier to teach and empower them to seek and receive quality care which is a fundamental right. This study will contribute greatly in helping patients to be informed about their rights should there be knowledge gaps to be discovered when using the research tool.